Pendekatan Psikologis dan Pendidikan Islam dalam Mengatasi Kesulitan Belajar Peserta Didik - Aulia Hafizoh; Vivik Shofiah; Khairil Anwar (STKIP Subang, 2026)
This study aims to examine students’ learning difficulties in terms of causal factors, psychological approaches, and handling strategies from the perspective of Islamic education. The research employed a library research method with a qualitative descriptive approach by collecting data from books, scientific journals, and relevant previous studies. The findings indicate that learning difficulties are influenced by both internal and external factors. Internal factors include learning motivation, psychological conditions, learning interest, and students’ cognitive abilities. Meanwhile, external factors include family environment, teachers’ instructional strategies, school environment, and social influences. Psychological approaches used to understand learning difficulties include behavioristic, cognitive, humanistic, and social approaches. The strategies for overcoming learning difficulties are carried out through early identification, differentiated learning, motivational support, learning guidance, and collaboration between teachers and parents. From the perspective of Islamic education, handling learning difficulties should be conducted humanistically by emphasizing compassion, guidance, and the holistic development of students’ potential so that the learning process can run effectively and optimally.